The Effects of Mixed Type Abnormal Respiratory Events on the Treatment of Obstructive Sleep Apnea Syndrome - Ceren Aliş; Gülçin Benbir Şenel; Derya Karadeniz (Türk Uyku Tıbbı Dergisi, 2021)

(untitled)
Objective:Central or mixed apneas may accompany obstructive apneas in patients with Obstructive Sleep Apnea syndrome (OSAS). There is scant evidence about the potential impact of mixed apneas on the therapy modalities. Here, apneas/hypopnoeas’ central and/or mixed effects on the positive airway pressure (PAP) modes chosen to be effective in patients with OSAS were evaluated.Materials and Methods:Patients who underwent a whole night polysomnography within last 2 years in our Sleep and Disorders Unit were consecutively examined. The patients included were those diagnosed with OSAS associated with central and/or mixed apneas. To determine the effective PAP modes, a second night polysomnography for titration was performed in these patients.Results:A total of 70 patients were included in the study, wherein 55 (78.6%) were males, with a mean age of 55.4±11.7 years. Continuous mode PAP (CPAP) therapy was effective in 60 patients (85.7%, group 1), whereas other modes (as BPAP-ST/ASV) were needed in 10 patients (14.3%, group 2). No statistically significant difference was found between the two groups in terms of gender, age or comorbid diseases (p=0.314, p=0.193 and p=0.081, respectively). Although BPAP-ST/ASV mode was needed in the presence of central apneas (p=0.039), CPAP mode was effective in OSAS patients with mixed apneas (p=0.055).Conclusion:The results showed that gender, age or comorbid conditions did not play a significant role in the determination of effective PAP mode. Mixed type abnormal respiratory events differed from central apneas/hypopnoeas as they did not require the use of BPAP-ST/ASV mode, and CPAP mode was effective enough in OSAS patients that manifested mixed type abnormal respiratory events.